A comparative study on electrochemical performance of KOH activated carbons derived from different biomass sources - Musa acuminata stem, Pongamia pinnata seed oil extract cake, cajanus cajan stem and Asclepias syriaca floss. Issue 4 (April 2023) - Byatarayappa, Gopalakrishna; G, Radhika M.; R, Srilakshmi; V, Tejashree; Venkatesh, Krishna; N, Nagaraju; Nagaraju, Kathyayini
Abstract: In the present scenario of research, the recycling of inexpensive widely available agricultural waste/biowaste to activate carbon (AC) and procurement of value-added product has significant impact on energy storage systems, particularly in Electrochemical double layer capacitors (EDLCs). Herein, we report the production of KOH activated carbons from different biomass sources such as Musa Acuminata stem (MAC), Pongamia pinnata seed oil extract cake (PPC), Cajanus Cajan stem (CCC) and Asclepias syriaca floss (ASC) for the said purpose. Initially, the biomass materials were pyrolyzed at 550 °C and then activated with KOH at 800 °C. All the carbon materials were characterized for their physico-chemical properties by various analytical techniques and compared. Further, these materials were studied for their electrochemical performance using suitable electro-analytical techniques in 1 M KOH solution. ACs (Activated carbons) derived from MAC, PPC, CCC & ASC were estimated in three electrode system and were found to exhibit a specific capacitance (Cs) of 358, 343, 355 & 540 F/g at a scan rate of 2 mV/s and 102, 188, 253 & 256 F/g at a current density of 2.5 A/g respectively. The main novel objective of this work is to correlate the morphological and surface properties of these ACs obtained from different biomass sources with electrochemical performance. A symmetric coin cell constructed with ASC material exhibited Cs of 67 F/g at a current density of 2.5 A/g with maximum energy & power densities (ED & PD) of 37.2 W h/kg and 19.9 kW/kg respectively. Further the cell showed 25, 000 cycles stability with 86% Cs retention and 100% coulombic efficiency.